1999
DOI: 10.1099/00207713-49-2-675
|View full text |Cite
|
Sign up to set email alerts
|

Nocardioides nitrophenolicus sp. nov., a p-nitrophenol-degrading bacterium

Abstract: 3 Japan Collection of A p-nitrophenol-degrading bacterial strain was isolated from industrial wastewater. This strain (NSP413 was identified as a member of the genus Nocardioides from c hemotaxonom i c characterizations and p h y I og enet ic inference based on 165 rDNA sequence analysis. The G+C content is 71.4 mol%.The diamino acid in the cell-wall peptidoglycan is u-diaminopimelic acid. The predominant menaquinone is MK=8(HJ. The cellular fatty acid profile is similar to those of Nocardioides species. 165 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
61
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 21 publications
9
61
1
Order By: Relevance
“…Tweens 20, 40 and 60 are hydrolysed. Acetate, L-malate, pyruvate and L-glutamate are utilized as sole carbon and energy sources and salicin is weakly utilized, but citrate, succinate, dData from Prauser (1976Prauser ( , 1984, Collins et al (1994), Yoon et al (1997Yoon et al ( , 1999Yoon et al ( , 2004 and Lawson et al (2000); a different result was reported by Yi & Chun (2004a). Table 1. cont.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…Tweens 20, 40 and 60 are hydrolysed. Acetate, L-malate, pyruvate and L-glutamate are utilized as sole carbon and energy sources and salicin is weakly utilized, but citrate, succinate, dData from Prauser (1976Prauser ( , 1984, Collins et al (1994), Yoon et al (1997Yoon et al ( , 1999Yoon et al ( , 2004 and Lawson et al (2000); a different result was reported by Yi & Chun (2004a). Table 1. cont.…”
contrasting
confidence: 41%
“…fatty acids representing >1 % of the total) comprised the following: branched fatty acids iso-C 16 : 0 (49.7 %), anteiso-C 17 : 0 (4.9 %), iso-C 17 : 0 (2.6 %), iso-C 18 : 0 (2.3 %), iso-C 15 : 0 (1.6 %) and iso-C 16 : 1 (2.3 %); unsaturated fatty acids C 18 : 1 v9c (7.4 %), C 17 : 1 v6c (5.4 %) and C 17 : 1 v8c (1.1 %); straight-chain fatty acids C 18 : 0 (2.3 %), C 17 : 0 (1.9 %) and C 16 : 0 (1.7 %); 10-methyl fatty acids C 18 : 0 (8.3 %), C 17 : 0 (2.9 %) and C 16 : 0 (1.8 %), and summed feature 3 (C 16 : 1 v7c and/or iso-C 15 : 0 2-OH) (1.6 %). This fatty acid profile is similar to those of Nocardioides species, although there are differences in the proportions of some fatty acids, perhaps because of differences in the extraction and cultivation conditions (Yoon et al, 1997(Yoon et al, , 1999(Yoon et al, , 2004(Yoon et al, , 2005aLawson et al, 2000;Yi & Chun, 2004a, b;Kubota et al, 2005). The DNA G+C content of strain DS-51 T was 71.1 mol%.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Cell-wall diamino acid was determined as described by Staneck & Roberts (1974). Most chemotaxonomical characters of strain JC2056 T were typical of the genus Nocardioides (Collins et al, 1994;Lawson et al, 2000;O'Donnell et al, 1982;Prauser, 1976Prauser, , 1986Suzuki & Komagata, 1983;Yoon et al, 1997Yoon et al, , 1999Yoon et al, , 2003); MK-8(H 4 ) as a major menaquinone, LL-DAP as a cell-wall diaminopimelic acid, 70 mol% as the DNA G+C content. The cellular fatty acid composition of our isolate also resembled that of other Nocardioides species, but was differentiated by high proportions of iso-16 : 0 (52?0 %) and iso-16 : 1 H (14?5 %).…”
mentioning
confidence: 99%
“…each constituted >10 % of total fatty acids) are iso-C 16 : 0 , 10-methyl C 18 : 0 and C 17 : 1 v6c, although there are differences in the proportions of some fatty acids, perhaps because of differences in extraction and cultivation conditions (Yoon et al, 1997(Yoon et al, , 1999(Yoon et al, , 2004(Yoon et al, , 2005aLawson et al, 2000;Yi & Chun, 2004a, b;Kubota et al, 2005). The DNA G+C content of strain A2-4 T was 72?1 mol%.…”
mentioning
confidence: 99%